2009
DOI: 10.1016/j.wear.2009.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Applications of CrAlN ternary system in wood machining of medium density fibreboard (MDF)

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. a b s t r a c tNowadays, medium density fibreboard (MDF) composite wood is more and more used in the furniture industry to replace bulk wood such as oak, beech, etc. Indeed, this material presents good mechanical properties, is easy to machine, homogeneous, exists in different dimensions (thickness, etc.), is cheaper than bulk wood and finally can be covered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
2
15
0
1
Order By: Relevance
“…However, low residual stresses (between À1 and À3.6 GPa) as obtained by Reiter et al [23] were determined, which promotes good adhesion of the CrAlN layers. In addition, these low residual stresses will enable us to deposit thick films (between 1.8 and 3 mm), which reduces cracks produced by alternating and thermal stresses, and leads to good mechanical and tribological properties [6].…”
Section: Mechanical Properties Of Deposited Layersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, low residual stresses (between À1 and À3.6 GPa) as obtained by Reiter et al [23] were determined, which promotes good adhesion of the CrAlN layers. In addition, these low residual stresses will enable us to deposit thick films (between 1.8 and 3 mm), which reduces cracks produced by alternating and thermal stresses, and leads to good mechanical and tribological properties [6].…”
Section: Mechanical Properties Of Deposited Layersmentioning
confidence: 99%
“…Hard coatings can protect the steel surface very efficiently from physicochemical attacks and delay the formation and propagation of thermal and mechanical cracks [1]. In recent years, chromium aluminum nitride (CrAlN), a ternary nitride obtained by incorporating Al into transition binary CrN thin coatings, has been intensively investigated [2][3][4][5][6][7][8][9][10][11]. CrAlN coatings have been reported to exhibit good oxidation-resistance with no compositional and structural changes after annealing at 800 C [5] and at 900 C [8], as both the chromium and aluminum could form protective oxides which suppressed diffusion of oxygen in the bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14] CrAlN exhibits thermal conductivity, which is lower than that of CrN, good tribological properties and high hardness. 15,16 It has been found that CrAlN film can form both Al 2 O 3 and Cr 2 O 3 protective layers on the surface at high temperatures, preventing further diffusion of oxygen into the bulk film 17 and thereby raising the film oxidation temperature to 900uC. 18 Therefore, CrAlN can be a promising candidate for high speed machining and other high temperature wear applications.…”
Section: Introductionmentioning
confidence: 99%
“…Os carbetos podem ser preparados com ângulos de corte apropriados, necessários para conferir melhor qualidade de acabamento da superfície comparativamente aos PCDs. Nos últimos dez anos, muitos trabalhos foram realizados nesta área, resultando em um aumento na vida útil das ferramentas através de recobrimentos protetores obtidos através de nitretação, deposição de carbetos e filmes de diamante [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Apesar do amplo uso de recobrimentos duros do tipo PVD (Physical Vapor Deposition) e CVD (Chemical Vapor Deposition) para aumentar a resistência à abrasão de ferramentas de corte, até o presente momento, eles não têm sido utilizados na área de usinagem da madeira em escala industrial devido, principalmente, ao problema da aderência.…”
Section: Introductionunclassified